Trial of brief intermittent neuroleptic prophylaxis for selected schizophrenic outpatients: clinical outcome at one year. Issue 6679 (15th April 1989) - Jolley, A. G.; Hirsch, S. R.; McRink, A.; Manchanda, R.
Abstract : A study was conducted to investigate a novel approach to the prophylaxis of schizophrenic relapse. The treatment strategy comprised brief intermittent courses of neuroleptic agents begun as soon as non-psychotic symptoms believed to be early signs of relapse appeared. Fifty four stable, remitted outpatients meeting the American Psychiatric Association's DSM-III criteria for schizophrenia were randomised double blind to receive brief intermittent treatment with either active or placebo depot neuroleptic injections. Only three patients given placebo injections and two controls were admitted to hospital during one year of follow up. Eight (30%) of the patients given placebo injections and only 2 (7%) of the controls, however, had a recurrence of schizophrenic symptoms. Patients given placebo injections experienced fewer extrapyramidal side effects and showed a trend towards a reduction in tardive dyskinesia. Dysphoric and neurotic symptoms were identified before eight out of 11 relapses, and these symptoms were more frequent in patients given placebo depot injections. These results suggest a viable but not necessarily better alternative to continuous oral or depot treatment for less ill, chronic, stabilised schizophrenics based on the early treatment of putative prodromal symptoms of relapse.